Dissolved Compounds Excreted by Copepods Reshape the Active Marine Bacterioplankton Community Composition - Valdés, Valentina P.; Fernandez, Camila; Molina, Verónica; Escribano, Rubén; Joux, Fabien (Frontiers in Marine Science, 2017)
Copepods are important suppliers of bioreactive compounds for marine bacteria through fecal pellet production, sloppy feeding, and the excretion of dissolved compounds. However, the interaction between copepods and bacteria in the marine environment is poorly understood. We determined the nitrogen and phosphorus compounds excreted by copepods fed with two natural size-fractionated diets (<20-µm and 20–150-µm) in the upwelling zone of central/southern Chile in late summer and spring. We then assessed the biogeochemical response of the bacterial community and its structure, in terms of total and active cells, to enrichment by copepod-excreted dissolved compounds. Results revealed that copepods actively excreted nitrogen and phosphorus compounds, mainly in the form of ammonium and dissolved organic phosphorus (DOP), reaching excretion rates of 2.6 and 0.05 µmol L-1 h-1, respectively. In both periods, the maximum excretion rates were associated with the 20–150-µm size fraction, but particularly during spring, when a higher organic matter quality was observed in excretion products compared to late summer. There were higher excretion rates of dissolved free amino acids (DFAAs) from copepods fed with the <20-µm size fraction, mainly histidine (HIS) in late summer and glutamic acid (GLU) in spring. A shift in the composition of the active bacterial community was observed between periods and treatments, which was associated with the response of the common seawater surface phyla Proteobacteria and Bacteroidetes. The specific bacterial activity (16S rRNA: rDNA) suggested a different response to the two size-fractionated diets. In late summer, Betaproteobacteria and Bacteroidetes were stimulated by the treatment enriched with excretion products derived from the 20–150-µm and <20-µm size fractions, respectively. In spring, Alphaproteobacteria were active in the treatment enriched with the excretion products of copepods fed with the <20-µm size fraction, whereas they were inhibited in the treatment enriched with excretion products in the 20–150-µm size fraction. Our findings indicate that different copepod diets can have a significant impact on the quantity and quality of their excretion compounds, which can subsequently generate shifts in the active bacterial composition. The bacterial response is probably associated with common-opportunistic sea surface microbes that are adapted to rapidly reacting to environmental offers.